2022
DOI: 10.1002/clc.23911
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation: Effective yet underutilized in patients with cardiovascular disease

Abstract: Cardiac rehabilitation is a comprehensive program that treats patients with multiple cardiac conditions including post‐myocardial infarction, stable angina, post‐coronary artery bypass surgery, chronic heart failure, and peripheral vascular disease with structured exercise, and nutrition and risk factor counseling. It is an effective tool that has been shown to improve not only quality of life but also reduce adverse cardiac events, including death. While the value of cardiac rehabilitation is supported by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…According to the 2022 AHA/ACC (American College of Cardiology)/Heart Failure Association (HFA) Guideline for the Management of Heart Failure, exercise training has been designated as a class 1 recommendation for certain cardiac patients whereas cardiac rehabilitation has been designated a class 2A recommendation for patients who wish to improve functional capacity, exercise tolerance, and health-related QOL [1 ▪▪ ]. In contrast, cardiac rehabilitation has been labeled as a class I indication for over a decade in patients following acute coronary syndrome (ACS), stable coronary artery disease and postcoronary artery bypass grafting (CABG) [2]. However, persistent disparities remain in referral rates as well as equitable access and participation for rehabilitation across patient subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2022 AHA/ACC (American College of Cardiology)/Heart Failure Association (HFA) Guideline for the Management of Heart Failure, exercise training has been designated as a class 1 recommendation for certain cardiac patients whereas cardiac rehabilitation has been designated a class 2A recommendation for patients who wish to improve functional capacity, exercise tolerance, and health-related QOL [1 ▪▪ ]. In contrast, cardiac rehabilitation has been labeled as a class I indication for over a decade in patients following acute coronary syndrome (ACS), stable coronary artery disease and postcoronary artery bypass grafting (CABG) [2]. However, persistent disparities remain in referral rates as well as equitable access and participation for rehabilitation across patient subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review and meta-analysis showed that CR reduces cardiovascular mortality, recurrent cardiac events, hospitalizations and improves health-related quality of life, highlighting the cost-effectiveness of CR ( 82 ). As such, the American Heart Association (AHA) and American College of Cardiology (ACC) consider CR a Class I indication for several cardiac conditions ( 83 ). Similarly, for patients with peripheral artery disease ( 84 ), the AHA/ACC has given Class I, Level A support for a supervised exercise program similar to cardiac rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation and practice of regular physical activity of moderate intensity would reduce the risk of cardiovascular mortality by 30%1 3 and would contribute to a significant improvement in quality of life, an increase in life expectancy, a reduction of the number of hospital admissions and a reduction in loss of autonomy 1 4. Despite the important proven benefits of physical activity and guidelines recommendations, only 30% of patients treated for a cardiovascular event (myocardial infarction, coronary revascularisation or heart failure) take part in a physical rehabilitation programme for 3 months in a cardiac rehabilitation centre 5–8. Several factors may explain the reluctance to engage in physical activity, such as inconvenient programme schedules, transportation restrictions, poor accessibility to practice sites and infrastructures, physical limitations or psychological barriers,9–11 as well as lack of motivation and time 12.…”
Section: Introductionmentioning
confidence: 99%